PENELUSURAN MAKNA, PERKEMBANGAN, DAN SUMBER PENAFSIRAN AL-QURAN DITINJAU DARI SUDUT PANDANG TEORITIS - Huda, Ali Anhar Syi'bul; Abdussalam, Aam; Husniah, Lu’lu; Salsabila, Shavira; Nurhuda, Abid (PT. Anagata Sembagi Education, 2024)
The Qu’ran as a guide to human life contains global norms and rules so a study is needed to detail what is contained in it. Along with the development of the era, the study of the Koran has reached various scientific fields, including the field of study of Al-Quran interpretation itself. This research aims to explain the search for the meaning of interpretation, development, and sources of interpretation of the Al-Quran from a theoretical point of view. The method used is descriptive qualitative with a literature study approach technique. The research results show that tafsir is an effort to understand the holy verses of the Koran through several methodologies and has been started since the time of the Prophet, where he was the initial interpreter in explaining the contents contained in the word of Allah to his people. Then after he died, the interpretation of Al-Quran verses continued to develop and the relay of studying these verses continued to the companions, continued back to the tabi'in, and continued exponentially until the modern and digital era. The sources for interpreting the Koran include verses from the Koran, hadiths of the Prophet, or the atsars of friends, then it can also be done with the ability of human reason, and finally with selective Islamic stories